Computational NX Fluid Structure Interaction (FSI) analysis on naval three way ball valve. Issue 1 (October 2021) - Dumitrache, C L; Deleanu, D
Abstract: This article represents the continuation of a study that was presented in another paper using the NX Siemens CAD program and FSI (fluid structure interaction analysis) for a complex valve encountered in the naval domain, a ball valve known as (three way ball valve -TWB). In designing of this valve presented in the previous work, some drawings (sketches) of the component parts presented in engineering guidelines were used, all dimensions being determined by the author. In the FSI analysis the same NX Siemens program was used to discretize the solid bodies of the valve coming into contact with the fluid, materials were chosen for these bodies, boundary conditions were set and the pressure field exerted by the fluid on the solid bodies was imported. Finally a series of conclusions were drawn about the speeds, pressures of the fluid and how they are distributed on the walls of the valve, determining the so-called structural analysis "fluid structure interaction".